Metodologi Pendidikan Islam Komprehensif - Sari Yulianti (LP2M Universitas PTIQ Jakarta, 2016)
This article discusses the comprehensive methodology of Islamic education lies underneath the parable verses sent down by Allah SWT., through the Qur’an and then elaborated and practiced by the Messenger of Allah in the form of Al-Hadith. Then the parables are combined with various modern educational methodologies that exist today. The results are the core of Islamic educational methodology summarized in terms of: good wisdom, good advice, and an elegant debate filling all the elements of modern educational methodology. By combining it is expected that a comprehensive Islamic education methodology will be able to further stimulate the implementation and technical education of these students.